Droplet microfluidic method for estimating the dynamic interfacial tension of ion-crosslinked sodium alginate microspheres; Langmuir; Vol. 40, iss. 30 - Piskunov M. V. Maksim Vladimirovich; Ashikhmin A. E. Alexander Evgenjevich; Kochkin D. Yu. Dmitry Yurjevich; Ronshin F. V. Fedor Valerjevich; Chen Longtsyuan (2024, 2024)
Title screen